2008
DOI: 10.1002/srin.200806135
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Chromium in Slags using MgO and Al2O3

Abstract: Chromium containing slags from stainless steelmaking may be leached by acidic environments, therefore they should be treated before being stockpiled or land filled. In this work, synthetic slags were prepared and the effect of CaO/SiO2, Cr2O3, MgO and Al2O3 contents on the stability of the mineralogical species formed was analysed. The morphology and composition of the slags were determined by XRD and SEM‐EDS, whilst their chemical stability was evaluated by leaching with an aqueous acetic acid solution. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…The leaching behaviors of various phases are quite different . It was well accepted that spinel phase is very stable in air and leaching of Cr from spinel phase is negligible . Therefore, modifications of stainless steel slag were proposed by many researchers to enrich Cr in spinel phase and stabilized the slag .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaching behaviors of various phases are quite different . It was well accepted that spinel phase is very stable in air and leaching of Cr from spinel phase is negligible . Therefore, modifications of stainless steel slag were proposed by many researchers to enrich Cr in spinel phase and stabilized the slag .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] It was well accepted that spinel phase is very stable in air and leaching of Cr from spinel phase is negligible. [5][6][7][8][9] Therefore, modifications of stainless steel slag were proposed by many researchers to enrich Cr in spinel phase and stabilized the slag. [5][6][7][8][9][10] Low basicity was reported to favor the formation of spinel.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mineralogical species present in the slags are soluble in aqueous media, such as merwinite, periclase, dicalcium silicate, and lime, although there are other phases, such as wustite, spinel, and glass, being considered as resistant to water dissolution [6][7]. The investigation of García-Ramos et al [8] also showed that the Cr leachability has been suppressed by the presence of MgO or Al2O3 in the slag system of CaO-SiO2-Cr2O3, with the efficiency of MgO for the leaching suppression higher than that of Al2O3, due to the stable binding for Cr in MgCr2O4. In addition, the mineralogical and microstructural analyses performed by Tossavainen et al [9] and Engström et al [10] have shown that merwinite (Ca3MgSi2O8), akermanite (Ca2MgSi2O7), gehlenite (Ca2Al2SiO7), and spinels were major phases in the EAF slag.…”
Section: Introductionmentioning
confidence: 99%
“…When the factor sp exceeded 5 wt%, Cr leaching fell below the German norm of 0.05 mg/l Cr in the leachate. In other studies [13,14], the additions of Al 2 O 3 (3-12 wt%) to a slag basicity of 1.6 was shown to significantly increase the spinel formation and the Cr in the spinel phase decreased as a function of Al 2 O 3 addition. Tossavainen and Forssberg [15] showed that the addition of spinel forming compounds, such as MgO, Al 2 O 3 and FeO, to the slag at high temperature does in fact decrease the level of Cr leaching.…”
Section: Introductionmentioning
confidence: 75%